DEVELOPMENT AND EVALUATION OF LAMOTRIGINE SOYA LECITHIN SOLID DISPERSION: IN VITRO AND PHARMACODYNAMIC INVESTIGATION - GAUTAM, SURESH; NIKALAJE, YOGESH; BHADRE, DARSHANA; TRIVEDI, RASHMI; UMEKAR, MILIND; TAKSANDE, JAYSHREE (International Journal of Applied Pharmaceutics, 2020)
Objective: Epilepsy is a common neurodegenerative disorder characterized by spontaneous and repeated attacks of convulsions. It requires immediate pharmacotherapy to prevent its progression to status epilepticus. However, most of the anticonvulsant drugs are poorly water-soluble and demonstrate the delayed onset of action. Thus there is a need to improve its solubility for the better pharmaceutical profile. The objective of the present investigation was to enhance the solubility of lamotrigine incorporating soya lecithin as a phospholipid carrier by solid dispersion technique Methods: Solid dispersions of lamotrigine were prepared with soya lecithin by the solvent method. The effect of concentration of phospholipid and solvents on aqueous solubility and dissolution profile of lamotrigine was analyzed. Results: Ethanol increased lamotrigine solubility with soya lecithin in ratio 5:1. X-ray diffraction and scanning electron micrograph indicated a smaller crystallite size of lamotrigine with fairly uniform size distribution in the lamotrigine-soya lecithin solid dispersion. The resultant solid dispersion also significantly delayed the onset of clonic convulsion (875.8 s) as compared to control (85.5 s) and offered complete protection (100%) against the pentylenetetrazole induced seizures in the rat as compared to control (33.33%). Also, solid dispersion with maximum drug content (77.68%) and dissolution rate (91.40%) was formulated as an orodispersible tablet and characterized for its pharmaceutical properties. Conclusion: It can be concluded that the solid dispersion of lamotrigine incorporated with soya lecithin demonstrated enhanced solubility and dissolution rate may have potential clinical application.